The impact of household consumption expenditure on GDP growth in the Kingdom of Saudi Arabia using data from 1980 to 2020 - Khoj, Haitham; Balila, Basel Yasser; Alzamzami, Hassam Adnan (Journal of Economic, Administrative and Legal Sciences, 2022)
The research aims to estimate the family consumption function in the Kingdom of Saudi Arabia and its impact on the Saudi GDP. Because of the importance of this in contributing to the economy from a macroeconomic perspective by reviewing economic theories and hypotheses that concerned the aspect of consumption. Time series data for the period 1980 to 2020 were used to estimate the household consumption function in the Kingdom of Saudi Arabia. The Granger causality test was used to find the relationship between GDP and household consumption expenditure. The results indicate that there is a causal relationship from one direction of household consumption spending to GDP, that is, it has a positive effect on growth.
Keywords: Granger's test of causality; household consumption; GDP; Saudi Arabia